2011
DOI: 10.1289/ehp.1003323
|View full text |Cite
|
Sign up to set email alerts
|

A Toxicogenomic Comparison of Primary and Photochemically Altered Air Pollutant Mixtures

Abstract: Background: Air pollution contributes significantly to global increases in mortality, particularly within urban environments. Limited knowledge exists on the mechanisms underlying health effects resulting from exposure to pollutant mixtures similar to those occurring in ambient air. In order to clarify the mechanisms underlying exposure effects, toxicogenomic analyses are used to evaluate genomewide transcript responses and map these responses to molecular networks.Objectives: We compared responses induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…Our findings are consistent with other studies showing that photochemical oxidation of similar chemical mixtures increases toxicity in cell culture models and elevates expression of inflammatory biomarker genes (Lichtveld et al, 2012;Rager et al, 2011). Previous in vitro studies using a gasphase-only exposure system have shown that gas-phase products of isoprene photooxidation significantly enhance cytotoxicity and IL-8 expression (Doyle et al, 2004(Doyle et al, , 2007.…”
Section: Biological Implicationssupporting
confidence: 92%
“…Our findings are consistent with other studies showing that photochemical oxidation of similar chemical mixtures increases toxicity in cell culture models and elevates expression of inflammatory biomarker genes (Lichtveld et al, 2012;Rager et al, 2011). Previous in vitro studies using a gasphase-only exposure system have shown that gas-phase products of isoprene photooxidation significantly enhance cytotoxicity and IL-8 expression (Doyle et al, 2004(Doyle et al, , 2007.…”
Section: Biological Implicationssupporting
confidence: 92%
“…A study in rats exposed to limonene ozone reaction products did demonstrate induction of inflammation and stress responses, associated with pulmonary pathology, but the exposure was not easily related to the real-world situation (Sunil et al, 2007). Evidence that oxidation of the primary organic aerosol alters (and might potentiate) its toxicity was recently reported by Rager et al (2011), who exposed an immortalized lung epithelial cell line to real world aerosols, either during the morning or the afternoon, the latter reflecting a more oxidized aerosol. The responses of the cells to these differing aerosols were profiled by transcriptomics, revealing a more robust transcriptional response as the primary aerosol aged.…”
Section: Rationalementioning
confidence: 99%
“…Fine particles (< 2.5 µm) are found to cause adverse health effects and premature mortality in people (Dockery and Pope III, 1994;Lelieveld et al, 2015). The relative contribution of primary and secondary particles to these health effects is still unknown, but there are indications that secondary particles can be even more hazardous than primary particles (Künzi et al, 2015;McWhinney et al, 2011;Rager et al, 2011). Therefore, both primary and secondary particle emissions must be taken into consideration when evaluating the health effects of particle emissions.…”
Section: Introductionmentioning
confidence: 99%